A prototype of Biology Experiment (Body Fluid Control and Management) using constructivism theory with multimedia environment / Siti Hajar Said - Said, Siti Hajar (2006)
Multimedia has the potential of providing biological science education novel learning environments and pedagogy application to foster student interest, involve students in the research process, advance critical and problem solving skills, and also develop conceptual understanding of biological topics. Biological experiment using constructivism theory with multimedia environment is an interactive, multimedia, problem-based module, on body fluid control and management system that focus on human heart. The process of constructing the module was follows the topic in the biology textbook that provided by Malaysia Secondary School, Kurikulum Bersatu Sekolah Menengah (KBSM). This module is developed for science student's secondary school and also suitable for anyone those want to know about body fluid control and management system. In designing this module, the examples and questions Avill be constructed based on the learning theory that is constructivism approach. The module will be following the constructivism theory which the students will be able to construct the solutions and finally come out with general ideas of what they have learned. Beside of that, the example of biology questions will be provided and suited the each subtopic which they will learn.